Proteasome in action: substrate degradation by the 26S proteasome. (30th April 2021) - Sahu, Indrajit; Glickman, Michael H.
Abstract : Ubiquitination is the major criteria for the recognition of a substrate-protein by the 26S proteasome. Additionally, a disordered segment on the substrate — either intrinsic or induced — is critical for proteasome engagement. The proteasome is geared to interact with both of these substrate features and prepare it for degradation. To facilitate substrate accessibility, resting proteasomes are characterised by a peripheral distribution of ubiquitin receptors on the 19S regulatory particle (RP) and a wide-open lateral surface on the ATPase ring. In this substrate accepting state, the internal channel through the ATPase ring is discontinuous, thereby obstructing translocation of potential substrates. The binding of the conjugated ubiquitin to the ubiquitin receptors leads to contraction of the 19S RP. Next, the ATPases engage the substrate at a disordered segment, energetically unravel the polypeptide and translocate it towards the 20S catalytic core (CP). In this substrate engaged state, Rpn11 is repositioned at the pore of the ATPase channel to remove remaining ubiquitin modifications and accelerate translocation. C-termini of five of the six ATPases insert into corresponding lysine-pockets on the 20S α-ring to complete 20S CP gate opening. In the resulting substrate processing state, the ATPase channel is fully contiguous with the translocation channel into the 20S CP, where the substrate is proteolyzed. Complete degradation of a typical ubiquitin-conjugate takes place over a few tens of seconds while hydrolysing tens of ATP molecules in the process (50 kDa/∼50 s/∼80ATP). This article reviews recent insight into biochemical and structural features that underlie substrate recognition and processing by the 26S proteasome.